Study On Telekom Malaysia Berhad - Shaari, Shamsul (2004)
Telekom Malaysia is the incumbent operators in telecommunications industry in Malaysia. This case study is to undertake the analysis of company currents position and its future directions. With the market liberalization and deregulations, Telekom is facing stiff competition from its rivals who are getting bigger market share in the growing industry.